Application, Advantages and Disadvantages of Galium Arsenide Detectors - شهین مرادنسب بدرآبادی; داریوش سرداری; میترا اطهری (بیولوژی کاربردی, 2016)
Particles or ray detectors are devices with which detect, trace or distinguish high energy particles. One of these detectors is Gallium arsenide (GaAs). Difficulties in producing consistently the thick layers with sufficiently low doping required for adequate depletion depth (>100 µm), however, precluded further development. Then, there has been renewed interest in detectors based on both bulk- and epitaxially- grown materials. Hence, aim of this study was studying characterization, application, advantages and disadvantages of Gallium arsenide (GaAs). Defects of GaAs can be classified under geometrical aspects (dimensionality) or under the aspect of their origin (intrinsic and extrinsic defects). When GaAs uses as X ray detector, absorption character, resistivity, mobility and lifetime, material uniformity used in detector, performance stability and processibility should be consider. Types of imaging detectors GaAs are detectors based on epitaxial GaAs, detectors based on (compensated) SI-GaAs, detectors based on Cr-compensated HR-GaAs. A good spectroscopic performance, high CCE values and good image quality can be achieved with detectors based on epitaxial GaAs. The material homogeneity was reported to be higher and local variations of material properties to be less pronounced than in bulk material. In addition, advances in flip-chip processing techniques for high-Z compound semiconductors give reason for hope for high pixel yields and thus good image quality.